A Simultaneous-Equation Model of Short-Run Determinants of the PKR/USD Exchange Rate - Hsing, Yu (Asian Economic and Financial Review, 2014)
This paper examines the determinants of the exchange rate between the Pakistani rupee (PKR) and the U.S. dollar (USD) based on a simultaneous-equation model consisting of demand for and supply of the U.S. dollar. Empirical results show that the PKR/USD exchange rate is positively associated with the real U.S. policy rate, real GDP in Pakistan, real U.S. stock prices and the expected PKR/USD exchange rate and is negatively affected by the real Pakistani discount rate, U.S. real GDP, and real stock prices in Pakistan. Hence, policy rates, real GDP or income, stock prices and expected exchange rates play important roles in exchange rate determination in the short run.